SNW1 enables sister chromatid cohesion by mediating the splicing of sororin and APC2 pre‐mRNAs. (25th September 2014) - van der Lelij, Petra; Stocsits, Roman R; Ladurner, Rene; Petzold, Georg; Kreidl, Emanuel; Koch, Birgit; Schmitz, Julia; Neumann, Beate; Ellenberg, Jan; Peters, Jan‐Michael
Abstract Although splicing is essential for the expression of most eukaryotic genes, inactivation of splicing factors causes specific defects in mitosis. The molecular cause of this defect is unknown. Here, we show that the spliceosome subunits SNW1 and PRPF8 are essential for sister chromatid cohesion in human cells. A transcriptome‐wide analysis revealed that SNW1 or PRPF8 depletion affects the splicing of specific introns in a subset of pre‐mRNAs, including pre‐mRNAs encoding the cohesion protein sororin and the APC/C subunit APC2. SNW1 depletion causes cohesion defects predominantly by reducing sororin levels, which causes destabilisation of cohesin on DNA. SNW1 depletion also reduces APC/C activity and contributes to cohesion defects indirectly by delaying mitosis and causing "cohesion fatigue". Simultaneous expression of sororin and APC2 from intron‐less cDNAs restores cohesion in SNW1‐depleted cells. These results indicate that the spliceosome is required for mitosis because it enables expression of genes essential for cohesion. Our transcriptome‐wide identification of retained introns in SNW1‐ and PRPF8‐depleted cells may help to understand the aetiology of diseases associated with splicing defects, such as retinosa pigmentosum and cancer.